Danish interests in regional security institutions in East Africa - Katja Lindskov Jacobsen; Johannes Riber Nordby (Danish Institute for International Studies (DIIS), 2013)
For the past decade peace and security in East Africa have gained increasing focus internationally. The region has experienced armed conflicts, civil wars, rebellion, drought and famine. Yet, at the same time, there is also an emerging ambition among a number of African states to handle security issues on the continent independently. Such ambitions have fostered a variety of military capacity building programmes supported by external donors. This report explores how Denmark up until now has sought to contribute to strengthening political and military security in East Africa. This has mainly been done through capacity building projects anchored in different regional security institutions. The report illuminates some of the risks that such capacity building projects might confront. Furthermore the report also points out some of the challenges that exist in the cooperation between the Ministry of Foreign Affairs of Denmark and the Danish Ministry of Defence. Finally, the concluding section of the report discusses some lessons learned and presents some considerations for future capacity building programmes in Africa.
Keywords: 300